(untitled) (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
This study examines the impact of normative digital readiness requirements, digital sovereignty, organizational controls, and professional behavioral skepticism, on the humanization of financial decision-making in the Syrian accounting environment. An analytical research design was employed using data collected from a purposive sample of accounting academics and practitioners in Syria. The proposed model and hypotheses were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4. The results indicate acceptable levels of reliability and validity of the measurement model. Findings further reveal that digital sovereignty, organizational controls, and professional behavioral skepticism all exert positive and statistically significant effects on the humanization of financial decision-making. Digital sovereignty shows the strongest impact, while the three constructs jointly explain 45.5% of the variance in the dependent variable. The study concludes that responsible AI adoption in accounting requires more than technological implementation; it depends on an integrated normative digital readiness framework that combines data sovereignty, regulatory governance, and behavioral safeguards to preserve human oversight and professional accountability in constrained environments.